Improved Powdery Mildew Resistance of Transgenic Nicotiana benthamiana Overexpressing the Cucurbita moschata CmSGT1 Gene - Guo, Wei-Li; Chen, Bi-Hua; Guo, Yan-Yan; Yang, He-Lian; Mu, Jin-Yan; Wang, Yan-Li; Li, Xin-Zheng; Zhou, Jun-Guo (Frontiers in Plant Science, 2019)
Powdery mildew (PM), which is mainly caused by Podosphaera xanthii, is a serious biotrophic pathogen disease affectiong field-grown and greenhouse-grown cucurbit crops worldwide. Because fungicides poorly control PM, the development and cultivation of PM-resistant varieties is critical. A homolog of SGT1 (suppressor of the G2 allele of skp1), which encodes a key component of the plant disease-associated signal transduction pathway, was previously identified through a transcriptomic analysis of a PM-resistant pumpkin (Cucurbita moschata) inbred line infected with PM. In this study, we have characterized this SGT1 homolog in C. moschata, and investigated its effects on biotic stress resistance. Subcellular localization results revealed that CmSGT1 is present in the nucleus. Additionally, CmSGT1 expression levels in the PM-resistant material was strongly induced by PM, salicylic acid (SA) and hydrogen peroxide (H2O2). In contrast, SA and H2O2 downregulated CmSGT1 expression in the PM-susceptible material. The ethephon (Eth) and methyl jasmonate (MeJA) treatments upregulated CmSGT1 expression in both plant materials. The constitutive overexpression of CmSGT1 in tobacco minimized the PM symptoms on the leaves of PM-infected seedlings, accelerated the onset of cell necrosis, and enhanced the accumulation of H2O2. Furthermore, the expression levels of PR1a and PR5, which are SA signaling transduction markers, were higher in the transgenic plants than in wild-type plants. Thus, the transgenic tobacco plants were significantly more resistant to Erysiphe cichoracearum than the wild-type plants. This increased resistance was correlated with cell death, H2O2 accumulation, and upregulated expression of SA-dependent defense genes. However, the chlorosis and yellowing of plant materials and the concentration of bacteria at infection sites were greater in the transgenic tobacco plants than in the wild-type plants in response to infections by the pathogens responsible for bacterial wilt and scab. Therefore, CmSGT1-overexpressing tobacco plants were hypersensitive to these two diseases. The results of this study may represent valuable genetic information for the breeding of disease-resistant pumpkin varieties, and may also help to reveal the molecular mechanism underlying CmSGT1 functions.